2010
DOI: 10.1177/1475921710365261
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-Acoustic Modulation Utilizing a Swept Probing Signal for Robust Crack Detection

Abstract: One practical issue that must be addressed prior to the implementation of a vibration-based structural health monitoring system is the influence that variations in the structure's environmental and boundary conditions can have on the vibration response of the structure. This issue is especially prominent in the structural health monitoring of aircraft, which operate in a wide variety of different environmental conditions and possess complex structural components connected through various boundary conditions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 31 publications
0
82
0
Order By: Relevance
“…One of the parameters to vary is the carrier frequency, both in amplitude and in frequency. Yoder et al [10] found a strong correlation between the amplitude of the carrier sidebands and the magnitude of the underlying spectral response of the damaged structure. This is supported by the theoretical single degree of freedom model (see section 1.…”
Section: Conclusion and Future Prospectmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the parameters to vary is the carrier frequency, both in amplitude and in frequency. Yoder et al [10] found a strong correlation between the amplitude of the carrier sidebands and the magnitude of the underlying spectral response of the damaged structure. This is supported by the theoretical single degree of freedom model (see section 1.…”
Section: Conclusion and Future Prospectmentioning
confidence: 99%
“…Traditional vibration based methods, relatively easy to implement, but suffering from a limited sensitivity [3,4], often rely on a linear system description, while more recent work also features nonlinear dynamic effects introduced by local defects [5,6]. Potential benefits are reported in terms of sensitivity [7][8][9] and environmental robustness [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, a lowfrequency pumping input and a high-frequency probing input are used in NWMS for creating modulation. Here, the amplitude of modulation heavily depends on the choice of the probing and pumping frequencies, and the optimal combination of these two input frequencies is also affected by environmental and operational conditions (e.g., temperature and loading) of the target structure and even by defect configurtions [7,[9][10][11]. Therefore, finding the optimal combination of the probing and pumping frequencies, which can maximize the modulation level, becomes a moving target.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, finding the optimal combination of the probing and pumping frequencies, which can maximize the modulation level, becomes a moving target. To find an optimal combination of the probing and pumping frequencies that can maximize the modulation level, frequency-swept probing signals and a frequency-fixed pumping signal are used [11].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the resulting modulated signal contains new frequency components, which are can be used to detect the defect in the structures. Yoder and Adams 20 proposed a swept probing signal to increase the applicability and robustness of the vibro-acoustic modulation technique in damage detection with experimental verification. Klepka et al 21 carried out an experimental investigation of the low-frequency vibration excitation on modulation intensity and associated nonlinear wave interaction mechanisms, which further enhanced the understanding of using the vibro-acoustic modulation technique in damage detection.…”
Section: Introductionmentioning
confidence: 99%